Both thyroid hormone levels and resting metabolic rate decrease in African striped mice when food availability decreases - Rimbach, R.; Pillay, N.; Schradin, C. (Company of Biologists Ltd, 2017)
In response to variation in food availability and ambient temperature (Ta), many animals show seasonal adaptations in their physiology. Laboratory studies showed that thyroid hormones are involved in the regulation of metabolism, and their regulatory function is especially important when the energy balance of an individual is compromised. However, little is known about the relationship between thyroid hormones and metabolism in free-living animals and animals inhabiting seasonal environments. Here, we studied seasonal changes in triiodothyronine (T3) levels, resting metabolic rate (RMR) and two physiological markers of energy balance (blood glucose and ketone bodies) in 61 free-living African striped mice (Rhabdomys pumilio) that live in an semi-arid environment with food shortage during the dry season. We predicted a positive relationship between T3 levels and RMR. Further, we predicted higher T3 levels, blood glucose levels and RMR, but lower ketone body concentrations, during the moist season when food availability is high compared with summer when food availability is low. RMR and T3 levels were negatively related in the moist season but not in the dry season. Both RMR and T3 levels were higher in the moist than in the dry season, and T3 levels increased with increasing food availability. In the dry season, blood glucose levels were lower but ketone body concentrations were higher, indicating a change in substrate use. Seasonal adjustments in RMR and T3 levels permit a reduction of energy expenditure when food is scarce, and reflect an adaptive response to reduced food availability in the dry season.
Keywords: Triiodothyronine; Metabolism; Energetics; Fasting; Starvation; Drought; African striped mice; MOUSE RHABDOMYS-PUMILIO